STUDI KETERLAKSANAAN PENDEKATAN SAINTIFIK PADA PROSES PEMBELAJARAN BIOLOGI DALAM IMPLEMENTASI KURIKULUM 2013 DI SMA NEGERI KOTA PALEMBANG - Binar Azwar Anas Harfian; Etty Nurmala Fadillah (Bioma : Jurnal Ilmiah Biologi, 2018)
Learning in the 2013 curriculum in schools is carried out using a scientific approach. The scientific approach is closely related to the scientific method. The scientific method is the root of the scientific approach which in practice is not separate from each other. The purpose of this study was to find out the feasibility of a scientific approach through observing, asking, trying or collecting information, associating, and communicating in the learning process of biology in Palembang City State High School. This research is included in survey research with quantitative and qualitative approaches. The study was carried out in 18 state high schools in the city of Palembang which have implemented the 2013 Curriculum. The research subjects consisted of 18 representatives of the school principal in the curriculum, 18 biology teachers who taught in class XI, and 1200 students in the XI class majoring in science. Teacher sampling was carried out by purposive sampling technique. Data collection instruments in this study include questionnaire sheets, observation sheets, interview sheets, and documentation. The results of this study are the implementation of a scientific approach to the learning process in the 2013 curriculum implementation in the Palembang category of Very Good City High School with the percentage for components observing as much as 76.84%, the asking component of 73.03%, the component trying / collecting information of 76.43 %, the associating component is 75.76%, and the component communicates as much as 79.45%.